2019
DOI: 10.1111/acel.12919
|View full text |Cite
|
Sign up to set email alerts
|

Tau underlies synaptic and cognitive deficits for type 1, but not type 2 diabetes mouse models

Abstract: Diabetes mellitus (DM) is one of the most devastating diseases that currently affects the aging population. Recent evidence indicates that DM is a risk factor for many brain disorders, due to its direct effects on cognition. New findings have shown that the microtubule‐associated protein tau is pathologically processed in DM; however, it remains unknown whether pathological tau modifications play a central role in the cognitive deficits associated with DM. To address this question, we used a gain‐of‐function a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 64 publications
(90 reference statements)
0
23
0
Order By: Relevance
“…While the two conditions share some attributes, the evidence linking AD to T2D is weak. The Rush longitudinal cohort study of aging found that neither HbA1c nor diabetes was correlated with plaque, tau, or infarct pathology ( Pruzin et al, 2017 ); cognitive and synaptic deficits in a model of T2D are independent of tau ( Trujillo-Estrada et al, 2019 ). T2D confers no elevation in the accumulation of Aβ or neurofibrillary pathology ( Beeri et al, 2005 ; Heitner and Dickson, 1997 ; Peila et al, 2002 ; Roberts et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the two conditions share some attributes, the evidence linking AD to T2D is weak. The Rush longitudinal cohort study of aging found that neither HbA1c nor diabetes was correlated with plaque, tau, or infarct pathology ( Pruzin et al, 2017 ); cognitive and synaptic deficits in a model of T2D are independent of tau ( Trujillo-Estrada et al, 2019 ). T2D confers no elevation in the accumulation of Aβ or neurofibrillary pathology ( Beeri et al, 2005 ; Heitner and Dickson, 1997 ; Peila et al, 2002 ; Roberts et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…These could be related to impaired insulin signaling in the brain resulting in tau hyperphosphorylation, one of the pathological features in AD. Several studies have shown insulin to regulate tau phosphorylation [ 11 , 18 , 19 ].…”
Section: Reviewmentioning
confidence: 99%
“…Postmortem studies have shown an increase in hyperphosphorylated tau in patients with DM compared to age-matched controls suggesting a link between DM and AD [ 18 ]. Additionally, western blot analysis has shown a significant increase in the total tau protein present in human patients with both DM and AD, in addition to non-significant hyperphosphorylation at the Ser202/Thr205 and pThr231 epitopes [ 18 ]. It has also been shown that insulin resistance increases as we age, leading to more susceptibility to diseases like AD [ 12 ].…”
Section: Reviewmentioning
confidence: 99%
“…These inflammatory mediators can activate brain-residing microglia and astrocytes, leading to CNS inflammation and synaptic dysfunction [ 23 ]. Recent study further demonstrated that insulin-signaling dysregulation and tau pathology are critical for T1DM-associated cognitive/synaptic deficits, while chronic inflammation plays an important role in T2DM-associated cognitive/synaptic impairments [ 2 ]. Therefore, alleviating inflammation may represent a promising therapeutic option to ameliorate cognitive dysfunction and dementia in both T2DM and AD.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) is the most common chronic metabolic disease characterized by insulin resistance and chronic inflammation, leading to hyperglycemia and accelerated aging [ 1 , 2 ]. Cognitive impairment is a well-known complication of T2DM; however, the precise mechanism through which T2DM metabolic disturbances contribute to cognitive decline remains uncertain.…”
Section: Introductionmentioning
confidence: 99%